Bopyrid isopods parasitizing on the cultured fresh water prawn, macrobrachium malcolmsonii in South India - Gopalakrishnan, Ayyaru Navaneetha; Raja, Kuzhanthaivel Kanmani; Trillers, Jean Paul; Rajkumar, Mani; Rahman, Mohammad Mustafizur (Springer India, 2017)
The bopyrid isopods are common in wild Macrobrachium spp. but not common in aquaculture condition. This is the first study that reports the parasitizing of bopyrid isopods on the cultured M. malcolmsonii. Bopyrid isopod (Probopyrus buitendijki) was identified in the branchial cavities of the freshwater prawn, M.malcolmsonii fromgrow-out culture pond at Kuriyamangalam, India. Macrobrachium malcolmsonii is a new host for P. buitendijki. A total of 1323 M. malcolmsonii were checked for this study. The overall prevalence of the parasitic infestation was reached 46.2 %. The parasitic infection was higher in female (83 %) than in male (3.4 %). Highest prevalence of infestation was found in the median size group (7–8 cm) (58.7 %). Infected females were not berried unlike uninfected prawns. The parasites cause infertility and does not found any organ deformities due to the infestation. The parasite was inversely attached in the gill chamber with no lesion on the gill but the infected branchial chamber became bulged.